Diagnostic Fine-Needle Biopsy of Small Solid Pancreatic Lesions Using a Franseen Needle during Endoscopic Ultrasound Examination - Takahashi, Kosuke (Diagnostics (Basel), 2020)
Background and aim: During endoscopic ultrasound-guided fine needle aspiration biopsy (EUS-FNB), Franseen needles can help collect sufficient tissue to permit histopathological assessment. However, its efficacy might be limited by the size of the targeted lesion. This study aimed to evaluate the feasibility of histopathological assessment of small solid pancreatic lesions using a 22-gauge Franseen needle during EUS-FNB. Methods: This retrospective study evaluated data from all patients who underwent EUS-FNB using a Franseen needle for solid pancreatic lesions at the University of Toyama Hospital between June 2018 and April 2020. Results: The study included 159 patients who had 152 malignant lesions and 7 benign lesions. The malignant lesions included pancreatic cancers (n = 134), neuroendocrine neoplasms (n = 15), metastatic tumors (n = 2), and a solid pseudopapillary neoplasm (n = 1). The diagnostic accuracy of EUS-FNB (combining histology and cytology) was 98.7%. However, the histopathological diagnosis was only confirmed for 64.3% of small lesions (<10 mm), relative to 97.2% for larger lesions. Multivariate analysis also revealed that lesion size of <10 mm predicted a less accurate histopathological diagnosis (odds ratio: 6.97, 95% confidence interval: 1.02–47.67; p = 0.041). Further analyses revealed a failed histological diagnosis in 4 patients with lesions of <5 mm in size and accurate diagnoses in 9 out of 10 patients with lesions of 5–10 mm in size. Conclusions: The diagnostic accuracy for small lesions (<10 mm), especially for lesions of <5 mm, based on histological examination alone, was significantly lower than that for others (>10 mm). Furthermore, multivariate analysis revealed that only lesion size was an independent predictor of histopathological diagnosis accuracy.